2016
DOI: 10.1037/lhb0000162
|View full text |Cite
|
Sign up to set email alerts
|

Predicting probation revocation and residential facility placement at juvenile probation review hearings: Youth-specific and hearing-specific factors.

Abstract: Although most justice-involved youth receive probation as a community-based alternative to residential facility placement, many of these youth are later committed to residential facilities when their probation dispositions are revoked at probation review hearings. The limited research investigating predictors of facility placement following juvenile probation revocation has focused primarily on youth-specific factors rather than on factors that can change from hearing to hearing, such as noncompliance with cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…Results of GEE analyses revealed that probation revocation was not significantly associated with any youth-specific characteristics (i.e., race, gender, age at hearing, number of previous referrals, or whether the youth was initially charged with a felony offense). Consistent with hypotheses about replicating prior work in this area (NeMoyer et al, 2016), results revealed that documentation of several noncompliant behaviors was significantly associated with probation revocation. These behaviors included incurring new charges (OR = 10.91), going AWOL from home or supervision (OR = 6.82), using drugs or alcohol (OR = 5.32), missing school (OR = 3.79), poor behavior at home or in the community (OR = 3.05), and problems related to a day/evening program (OR = 2.64).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Results of GEE analyses revealed that probation revocation was not significantly associated with any youth-specific characteristics (i.e., race, gender, age at hearing, number of previous referrals, or whether the youth was initially charged with a felony offense). Consistent with hypotheses about replicating prior work in this area (NeMoyer et al, 2016), results revealed that documentation of several noncompliant behaviors was significantly associated with probation revocation. These behaviors included incurring new charges (OR = 10.91), going AWOL from home or supervision (OR = 6.82), using drugs or alcohol (OR = 5.32), missing school (OR = 3.79), poor behavior at home or in the community (OR = 3.05), and problems related to a day/evening program (OR = 2.64).…”
Section: Resultssupporting
confidence: 86%
“…Interestingly, no youth-specific characteristics (e.g., race, gender, age, criminal history) demonstrated a significant relationship with probation revocation. Nonsignificant findings regarding gender and race align with previous literature (e.g., Kong & AuCoin, 2008; Leiber & Peck, 2013; NeMoyer et al, 2016) that failed to observe such group differences. Furthermore, the overall lack of significant static youth-related factors might indicate that dynamic need factors—as illustrated by the many significant noncompliant behaviors—appear to be particularly important for predicting probation revocation as an adverse outcome.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations